Direct Growth of 5 in. Uniform Hexagonal Boron Nitride on Glass for High‐Performance Deep‐Ultraviolet Light‐Emitting Diodes. Issue 18 (1st July 2018) - Li, Qiucheng; Wu, Qingqing; Gao, Jing; Wei, Tongbo; Sun, Jingyu; Hong, Hao; Dou, Zhipeng; Zhang, Zhepeng; Rümmeli, Mark H.; Gao, Peng; Yan, Jianchang; Wang, Junxi; et al.
Abstract: The direct coating of 2D hexagonal boron nitride (h‐BN) on insulating solid glass will endow glass with advanced properties, thus offering killer applications of the new type hybrid of h‐BN glass. However, daunting challenges still remain regarding the direct growth methodology of h‐BN on glass. Herein, a catalyst‐free chemical vapor deposition route for the direct synthesis of 5 in. uniform h‐BN thin films on functional quartz and sapphire glass is developed. The optical transparency, surface wetting, and thermal conductivity of glass are readily tailored by varying the deposited h‐BN thicknesses from monolayer to over 20 layers. Encouragingly, the as‐obtained h‐BN/sapphire glass can serve as a stress‐releasing substrate for the van‐der‐Waals epitaxial growth of AlN functional layers, as well as a thermal conductive template for constructing high‐performance deep‐ultraviolet light‐emitting diodes. This work hereby provides a brand new direction for the application of h‐BN glass in next‐generation solid‐state lighting devices. Abstract : Large‐scale uniform hexagonal boron nitride films are directly synthesized on two types of daily used glass (i.e., quartz and sapphire). The as‐obtained hexagonal boron nitride glass exhibits excellent optical transparency, ultraflat surface, as well as good thermal conductivity, which is employed as a perfect stress‐releasing substrate for the van‐der‐Waals epitaxial growth of AlN layers in high‐performance deep‐ultraviolet light‐emitting diodes.